Kajian Kriminologi Terhadap Tindak Pidana Pencurian Dengan Kekerasan Yang Dilakukan Oleh Anak - Badaru, Baharuddin; Sutiawati, Sutiawati (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
This study aims to identify and analyze the factors that cause violent crimes committed by children in Makassar City. This research method uses empirical legal research methods with primary and secondary data. The results of this study indicate, first, that the factors that cause the crime of theft with violence committed by children in Makassar City are caused by three main factors, namely social and environmental factors, instant mindset factors, and family dysfunction. In addition to these main factors, there are supporting factors that influence the occurrence of theft with violence by children in Makassar City, namely the victim factor, especially women who are mostly the targets of the perpetrators. Second, the efforts made by the National Police to prevent the occurrence of criminal acts of theft with violence committed by children in Makassar City have three main efforts, namely pre-emptive efforts, preventive efforts and repressive efforts in preventing the crime of theft by violence. by children. Recommendations or suggestions for this research are in making efforts to prevent theft with violence committed by children in Makassar City, it requires the cooperation of all parties to encourage the creation of peace and suppress the level of violent theft committed by children in Makassar City. . Then the role of law enforcement in providing treatment by imposing criminal sanctions indirectly, or imposing punishment in the form of punishment for children who commit theft with violence must be further enhanced, the punishment given must provide a deterrent effect and raise awareness of the perpetrator to improve his life, so that the perpetrators are punished. later have no intention to repeat or commit the crime.